2008
DOI: 10.1038/sj.bjp.0707638
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic depression of NMDA receptor‐mediated transmission by ketamine, ketoprofen and L‐NAME combinations in neonatal rat spinal cords in vitro

Abstract: Background and purpose: Spinal N-methyl-D-aspartate (NMDA) receptor/cyclooxygenase (COX) and nitric oxide synthase (NOS) pathways play a major role in nociceptive processing, and influencing them simultaneously may induce synergistic analgesia. This study determined the spinal antinociceptive interactions between ketamine (NMDA receptor channel blocker), ketoprofen (COX inhibitor) and L-NAME (NOS inhibitor) combinations. Experimental approach: Using an in vitro neonatal rat spinal cord preparation, two A-fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Ketoprofen inhibits both COX‐1 and COX‐2 isoforms. It has been shown to depress responses to low‐ and high‐intensity stimuli to the same extent and with similar EC 50 with only a minor reduction in the MSR .…”
Section: Modulation Of Spinal Reflexes By Analgesic Compoundsmentioning
confidence: 81%
“…Ketoprofen inhibits both COX‐1 and COX‐2 isoforms. It has been shown to depress responses to low‐ and high‐intensity stimuli to the same extent and with similar EC 50 with only a minor reduction in the MSR .…”
Section: Modulation Of Spinal Reflexes By Analgesic Compoundsmentioning
confidence: 81%
“…administration of acetic acid), Morgan et al demonstrated synergistic interaction between L-NAME and fl urbiprofen/indomethacin [16]. Ketoprofen and L-NAME co-infused in vitro, signifi cantly inhibited the production of a highly-sensitive excitatory postsynaptic potential, which is obtained by electrical stimulation of the isolated spinal cord of neonatal rats [28]. However, there are literature data that show the opposite effect, i.e.…”
Section: Discussionmentioning
confidence: 93%